2018
DOI: 10.7324/japs.2018.81019
|View full text |Cite
|
Sign up to set email alerts
|

Bunium persicum (Boiss.) B. Fedtsch: An overview on Phytochemistry, Therapeutic uses and its application in the food industry

Abstract: Bunium persicum (Boiss.) B. Fedtsch as a plant of the Apiaceae family grows in different regions of Asia such as Central Asia, Iran, Pakistan, Afghanistan, and India. This plant has significant medicinal, antimicrobial and antioxidant properties which indicate its high potential for use in the medicine and food industry. In traditional medicine, it is used to treat or improve some cases such as digestive and urinary disorders, diabetes, obesity and increasing breast milk. A comprehensive literature review was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(7 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…In corroboration with our results, Hassanzadazar et al (2018) also concluded that B. persicum could be used as a natural alternative to synthetic antioxidants based on the results of PV and TBA values of their investigation (Hassanzadazar et al, 2018).…”
Section: Av Pv Tba Values and Os Analysis Of Different Iao Treatmentssupporting
confidence: 88%
See 2 more Smart Citations
“…In corroboration with our results, Hassanzadazar et al (2018) also concluded that B. persicum could be used as a natural alternative to synthetic antioxidants based on the results of PV and TBA values of their investigation (Hassanzadazar et al, 2018).…”
Section: Av Pv Tba Values and Os Analysis Of Different Iao Treatmentssupporting
confidence: 88%
“…Z. tenuior (Bakhtiar et al, 2021) and F. angulata (Ghasemi Pirbalouti et al, 2016) are widely distributed in Iran. Also, B. persicum grows in areas with a Mediterranean climate such as Central and Western Asia (e.g., Iran) (Hassanzadazar et al, 2018). Due to their phenolic and flavonoid compounds, these plants have antioxidant and antibacterial activities, and gastrointestinal transit accelerating properties (Amiri and Joharchi, 2016;Dakah et al, 2019;Ehsani et al, 2016;Hazrati et al, 2019;Mahboubi, 2019).…”
Section: Preparation Of the Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…This plant is popular as a spice [ 352 ]. The roots and seeds are used as spices that provide flavor to the food [ 360 ]. About 70% of the world’s cumin is produced in India (725.42 thousand tons) [ 104 ].…”
Section: Ethnobotanical Knowledge Related To Spices and Herbsmentioning
confidence: 99%
“…Fedtsch. ), which is widely distributed in Central and Western Asia and in some regions of Europe, North Africa, and South America (Hassanzadazar et al, 2018). The species is an herbaceous perennial with small white flowers and a height of 30 to 80 cm.…”
Section: Introductionmentioning
confidence: 99%